Peran Pendidik PAUD dalam Pembentukan Karakter Anak Usia Dini di Era Teknologi Digital - Erita, Sukma; Witalia, Witalia; Ramadanti, Tifa (Jurnal Kridatama Sains dan Teknologi, 2025)
This study aims to analyze the role of educators in shaping the character of early childhood in the digital technology era in Tenggarong City. A qualitative descriptive approach was employed, with data collected through in-depth interviews and observations of early childhood educators who play a role in character formation. The findings indicate that educators can optimize the use of digital technology in a positive manner to support children's character development. Additionally, early childhood educators have responsibilities in character building, including serving as role models, providing supervision and guidance, and integrating character values into learning activities. Several key types of character development in early childhood were identified, including religious character, discipline and responsibility, social awareness and empathy, independence and creativity, as well as digital ethics. Collaboration with parents is also a crucial element in fostering children's character. Thus, this study seeks to identify and explore the roles that can be undertaken to build children's character through digital technology utilization. Alongside technological advancements, there are not only challenges but also opportunities, such as creating a supportive learning environment by leveraging technology creatively. This study concludes that educators play a key role in shaping the character of early childhood, particularly in addressing the challenges of the digital technology era. The implications of these findings emphasize the importance of establishing a supportive learning environment and integrating character values into education as a strategic approach to ensuring children's moral, ethical, and social development